2023
DOI: 10.53796/hnsj4527
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Antenatal Care Services at the Primary Healthcare center, Gezira, State, Sudan [June 2022–September 2022]

Abstract: Quality is the most important issue and the main predictor variable in developing as well as developed countries to achieve the Sustainable Development Goals. Sudan, which is the largest country in Africa, has one of the highest rates of maternal and perinatal mortality, project of safe motherhood in Gezira ,State Sudan lead to reduction of maternal death from 469 per 100,000 live births in 2005 to 139 in 2019, Still in recent years the percentage of maternal death increase so this area need many researches to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…To highlight the problem of ANC quality, in 2022 another study was conducted to assess pregnant women's experience of care and their satisfaction at the primary healthcare center in Gezira, Sudan. They concluded that the poor quality of ANC is due to inadequate material resources, a deficiency of human power, the absence of on-the-job training for service providers, insufficient protocols and guidelines, poor infrastructure, and administrative weakness at health facilities [23]. Another study conducted in 2011 at Ribat University Hospital in Khartoum was conducted to assess the quality of documentation for the ANC card.…”
Section: Quality Of Ancmentioning
confidence: 99%
“…To highlight the problem of ANC quality, in 2022 another study was conducted to assess pregnant women's experience of care and their satisfaction at the primary healthcare center in Gezira, Sudan. They concluded that the poor quality of ANC is due to inadequate material resources, a deficiency of human power, the absence of on-the-job training for service providers, insufficient protocols and guidelines, poor infrastructure, and administrative weakness at health facilities [23]. Another study conducted in 2011 at Ribat University Hospital in Khartoum was conducted to assess the quality of documentation for the ANC card.…”
Section: Quality Of Ancmentioning
confidence: 99%